(untitled) - Buck, Carol J. (St. Louis, 2017)
Select diagnosis codes accurately with Carol J. Buck'||chr(39)||'s 2017 ICD-10-CM: Standard Edition. Designed by coders for coders, this practical manual includes all the ICD-10 codes needed for basic outpatient and physician office coding. As coders need more extensive knowledge to code with ICD-10-CM ― and to choose from the thousands of possible codes ― this edition provides an essential background in A&P, pathology, and medical terminology, along with colorful Netter’s Anatomy illustrations and clear instructions for using the book. Together, these features make diagnosis coding faster and easier. Also included is a companion website with the latest coding news and updates!
Keywords: Phân loại quốc tế về bệnh,International classification of diseases